Studies on the heme oxygenase-1 pathway and anti-angiogenic factors in preeclampsia and endothelial protection - Ramma, Wenda (The University of Edinburgh, 2011)
The endothelium plays a pivotal role in the maintenance of vascular homeostasis and its dysregulation promotes vascular complications. This thesis proposes that heme oxygenase-1 (HO-1), an anti-inflammatory enzyme with antioxidant properties, is endothelial protective factor that prevents endothelial injury induced by cisplatin or activated neutrophils. Specifically, this thesis aimed to test (i) that overexpression of HO-1 prevents cisplatin-induced endothelial injury and suppresses caspase activity; (ii) whether neutrophil-endothelial cell activation resulted in the release of soluble Flt-1 (sFlt-1) and soluble endoglin (sEng), the two anti-angiogenic factors known to induce the clinical signs of preeclampsia; (iii) whether HO-1 prevented activated neutrophils from stimulating the release of these factors from the endothelium; (iv) the relative contribution and the co-dependency of neutrophil activation and anti-angiogenic growth factors in preeclampsia where systemic endothelial dysfunction is known to occur. This thesis shows that cisplatin inhibited human umbilical vein endothelial cells (HUVEC) metabolism as measured by MTT assay and resulted in the release of placenta growth factor (PlGF). Immunoblotting confirmed that cisplatin increased cleaved caspase-3 expression in HUVEC. These effects of cisplatin were attenuated in HUVEC infected with adenovirus encoding HO-1 and the effects were exacerbated when HO-1 was silenced by siRNA. Furthermore, cisplatin stimulated PlGF release was suppressed by the overexpression of HO-1. In addition, HO-1 overexpression inhibited angiogenesis as determined by vascular endothelial growth factor-induced capillary tube formation on Matrigel coated plates. Thus these studies indicate that agents which upregulate HO-1 could increase the effectiveness and tolerability to cisplatin in cancer treatment. Although neutrophils are early contributors to endothelial cell activation, no studies have determined their contribution to the release of sFlt-1 and sEng. We therefore investigated the effect of activated neutrophils on the release of sFlt-1 and sEng in endothelial/neutrophil co-cultures and in the circulation of women with normal pregnancy and preeclampsia. LPS-mediated neutrophil activation stimulated the release of sEng but not sFlt-1 from endothelial cells in culture. In the absence of neutrophils, overexpression of HO-1 in HUVEC downregulated the release of sEng. In contrast, HO-1 overexpression failed to inhibit the release of sEng in the presence of activated neutrophils. The release of sEng by activated neutrophils-endothelial cell cocultures appears to be mediated by metalloproteinases (MMP) as the broad-spectrum MMP inhibitor (GM6001) attenuated sEng release. Clinical studies demonstrated that sEng, pro-inflammatory interleukin-6 (IL-6) and the soluble markers of neutrophil activation (α-defensins and calprotectin) were all elevated in women with preeclampsia. We identified a direct correlation between neutrophil activation and IL-6 release. However, no correlation could be established between these factors and sEng release in preeclampsia. Hence, these results provide compelling clinical evidence to show that the increase in neutrophil activation and IL-6 release during preeclampsia are unlikely to significantly contribute to the clinical signs of preeclampsia as they fail to correlate directly with the anti-angiogenic factors, which form the final common pathway to the clinical signs of preeclampsia and systemic endothelial dysfunction.
Keywords: heme oxygenase; preeclampsia; neutrophil activation; endothelial cell biology